A cross-national study of teacher's perceptions of online learning success. (2nd January 2016) - Barberà, Elena; Gómez-Rey, Pilar; Fernández-Navarro, Francisco
Abstract: This study examines success factors in online learning from the instructors' perspective. Academic success comprises not only student satisfaction and good grades, but also perception of learning and knowledge transfer. A systemic model of inputs–process–outputs of learning was used. A total of 322 online teachers from four different universities and countries were used to study factors of attainment. Findings suggest that: (i) instructors from the University of Peking and the Autonomous Popular University of the State of Puebla reported learner factors as the most important for students on online courses, (ii) instructors from the University of New Mexico perceived institutional factors as the most important for establishing effective online learning and (iii) instructors from the Open University of Catalonia reported outcome factors as the most important for learners in online courses. Compared with other research results in online learning, instructors in this study generally reflect a greater concern about the content, social presence, instruction and their interactions than about technological matters.